Pemahaman Hadis di Ormas NU: Analisis terhadap Penerapan Hadis Dhaif di NU - Daib Insan Labib, Muhammad Alfreda (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2024)
This paper discusses NU’s method of understanding hadith dhaīf and its application. The focus of the study is in the form of a brief discussion of hadith understanding, information related to NU, and applications of the use of NU hadith along with examples. This method of writing is descriptive analysis, where data sets are described and then analyzed to achieve research objectives. The conclusions of this study, namely 1). NU understands hadith not through the text of the hadith directly but through the understanding of salaf ulama’s. 2). NU in understanding hadith can be considered tawasuth or even tasahul. 3). Indicators that strengthen the understanding of hadith in NU that are considered tawasuth or even tasahul. 4). Stages of falsification in understanding hadith. First, knowing the quality and quantity of hadith used by previous scholars in concluding a law. By looking at the reference directly (in this case what is meant is the primary book of hadith). Second, knowing the legal conclusions of a particular hadith, whether it is still relevant or not. Third, by falsifying, various kinds of understanding can be known from the same source.